Design of a Combined Solar Powered Pasture Chopping and Conveying Machine. - Kanyamumba Liberty (Kabale University, 2023)
Developing countries rely on agriculture as the backbone of their economies. However, agriculture in such countries is still lagging due to various reasons which include poor methods of farming, poor crop and animal breeds among others. Due to reasons like Land shortage, there has been advancements in livestock keeping by adopting zero grazing where animals can be fed and monitored from a confined place. Zero grazing provides advantages like Animals are kept inside hence more secure, feeds are utilized well, reduces pasture damage, maximum use of land, urban and peri-urban farmers can keep cattle, many animals can be fed from a small area, easy collection of manure, crop and biogas production, and easy detection of heat in animals. [1]. In addition to these, animal health management is assured through provision of good quality nutritious feeds, clean water, comfortable environment and reliable veterinary services which are essential for increased animal productivity due to reduced animal morbidity and mortality. [2] Since animals are confined in one place, it means that one has to prepare pasture for the livestock and feed them from where they are confined from. There are various methods of preparing pasture for the livestock which include; traditional method where the farmer uses a local tool commonly a panga to chop pasture, use of powered AC machines and manual chopping machines. All these methods present various number of challenges as cited in the literature and they call for the design of a solar powered pasture chopping and conveying machine to address these challenges. The study sought to design a solar powered pasture chopping and conveying machine to address the challenges being faced and utilization of renewable energy (solar energy)